2020
DOI: 10.1136/bmj.m2206
|View full text |Cite
|
Sign up to set email alerts
|

Intake of whole grain foods and risk of type 2 diabetes: results from three prospective cohort studies

Abstract: Abstract Objective To examine the associations between the intake of total and individual whole grain foods and the risk of type 2 diabetes. Design Prospective cohort studies. Setting Nurses’ He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 59 publications
3
110
0
1
Order By: Relevance
“…This is because cell walls, and the 3D matrix of the plant cell walls, affect the functional properties of ‘fibre’ impacting on the digestibility of the cell contents [ 5 ]. This may be part of the reason for the strong benefits seen in wheat fibre in cohort studies, despite the lack of effect seen in the short-term clinical trials for cardiovascular risk factors [ 19 , 20 , 21 , 22 ]. In randomised controlled trials comparing refined and wholegrain cereal foods, when the particle size of the fibre is made too small, the plant cell wall integrity and tissue architecture may be lost.…”
Section: Health Benefitsmentioning
confidence: 99%
“…This is because cell walls, and the 3D matrix of the plant cell walls, affect the functional properties of ‘fibre’ impacting on the digestibility of the cell contents [ 5 ]. This may be part of the reason for the strong benefits seen in wheat fibre in cohort studies, despite the lack of effect seen in the short-term clinical trials for cardiovascular risk factors [ 19 , 20 , 21 , 22 ]. In randomised controlled trials comparing refined and wholegrain cereal foods, when the particle size of the fibre is made too small, the plant cell wall integrity and tissue architecture may be lost.…”
Section: Health Benefitsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis of randomized controlled trials found that, compared with white rice, brown rice led to an improvement in triacylglycerol levels (-1.6 mg/dL) in interventions ranging Accepted manuscript from 150 to 400g of cooked rice (39) . One serving of brown rice per day was also associated with reductions in type 2 diabetes risk (Hazard ratio [HR] 0.72) in three large prospective studies from the United States of America (USA); however the association was no longer significant after adjusting for BMI (40) . For whole-wheat bread, there are also consistent beneficial effects reported.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-grain wheat intake has been promoted for its beneficial health effects already since the 1900s, when Dr. Thomas Allinson advocated Allinson bread for a healthier lifestyle. In population studies, increased intake of whole grain has been convincingly shown to be associated with a lower risk of a range of chronic diseases and overall mortality [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In most cohort studies (all except for Nordic European populations), wheat is the main source of grains.…”
Section: Whole-grain Wheat and Its Health Effectsmentioning
confidence: 99%